ASSESSMENT OF EFFICACY OF A VITAMINE PREPARATION ENRICHED WITH CALCIUM IN CHILDREN WITH VARIOUS TYPES OF ORTHOPEDIC PATHOLOGY - N.I. Taibulatov (Union of pediatricians of Russia, 2009)
The article provides information on the efficacy of a multivitamin complex enriched with calcium and magnesium in children with orthopedic pathology. It highlights that incorporating a multivitamin complex into the course of rehabilitation treatment for children with various types of faults in posture and platy podia dramatically enhances the efficacy of therapy. The children who were administered the preparation had significantly improved parameters of endurance under exercise stress conditions in comparison with similar parameters in children, whose course of rehabilitation treatment did not include the multivitamin complex. The control study of the feet planta's status using the computerized system in children from the main group where the preparation was administered, found improved podo scopy parameters by 65% compared with the benchmark group where subjects did not received the multivitamin complex.Key words: children, multivitamin, posture, platypodia, rehabilitation treatment.